Variation of diagnosis and treatment of catheter-associated urinary tract infections: an online survey among caretakers involved - Tess van Doorn; Sophie A. Berendsen; Rosa L. Coolen; Jeroen R. Scheepe; Bertil F. M. Blok (Therapeutic Advances in Urology, 2023)
Background: The diagnosis of a clinically significant catheter-associated urinary tract infection (CAUTI) in patients performing clean intermittent catheterization (CIC) or with an indwelling catheter (IC) can be challenging. Objective: To get an insight into the variation of the used definition, diagnosis and management of CAUTIs by relevant healthcare workers in the Netherlands. Design: An online clinical scenario-based survey. Methods: The survey was built in Limesurvey and distributed to healthcare workers from randomly selected urology departments, rehabilitation departments/centres and general practice offices between January and May 2022. Questions regarding their field of experience, management strategies, used guidelines and two hypothetical cases with clinical scenarios of a possible CAUTI were included. Results: A total of 172 individuals participated, of which 112 completed the survey. In all, 32 individuals who completed the survey partially were also included. Participants consisted of 68 [44 urologists, 22 rehabilitation doctors (RDs) and 2 general practitioners (GPs)] doctors, 60 nurses (46 from the urology department and 14 from rehabilitation centres/departments) and 16 medical assistants (13 from urology department and 3 from GP offices). The majority consulted patients with an IC or on CIC on a daily/weekly or monthly basis. In all, 35 urologists (79.5%), 9 RDs (40.9%), 21 (45.7%) nurses in the urology department and 6 (42.9%) nurses from a rehabilitation department/centre indicated bladder irrigation as a treatment option for prevention/treatment of CAUTIs, treatment of symptoms or treatment of blockage of the catheter. In the clinical scenarios presented, treatment discrepancies were seen between subspecialties and healthcare workers. Various guidelines were named for the definition of CAUTIs. Conclusion: A considerable variation in diagnoses and management of CAUTIs between the healthcare workers involved was seen. Uniformity in diagnosing and managing CAUTIs, to prevent overtreatment and possible resistance to antibiotics, is advised. Suitable multidisciplinary guidelines are preferred.